P11 Sputum neutrophil activity in asthma. (12th November 2019) - Barber, CGM; Ward, JA; Lau, LC; Gove, K; Elliott, SP; Brown, T; Rupani, H; Hinks, TSC; Kurukulaaratchy, RJ; Djukanovic, R; Chauhan, A; Staples, K; et al.
Abstract : Background: An abundance of neutrophils in sputum is associated with poor disease control1 . In contrast to eosinophils, the role of neutrophils in asthma is poorly understood. Sputum neutrophil activity rather than proportions may provide a better insight into disease activity. Objective: The purpose of this analysis was to explore the relationship between sputum markers of neutrophil activity, symptoms and lung function in asthma. Methods: 23 mild asthma and 159 severe asthma patients recruited to the Wessex severe asthma cohort study underwent complex characterisation including spirometry, questionnaires and sputum induction. Sputum analysis included protein assays and differential cell counts. Myeloperoxidase (MPO) and Neutrophil Elastase (NE) were measured as markers of neutrophil activity using singleplex ELISA. Correlation analysis of lung function and asthma control with sputum measures were completed using Spearmans rho. Results: Weak correlations were found between lung function and sputum measures. However, neutrophil activity had a stronger relationship with lung function than neutrophil proportion. Asthma control (ACQ6) had a very weak correlation with sputum neutrophil proportion but a weak significant relationship with markers of neutrophil activity. Conclusion: Neutrophil activity in sputum is more reflective of lung function and asthma control than sputum neutrophil proportion in asthma. Markers of neutrophil activity, rather than neutrophils per se, may more accurately reflect the inflammatory processes in poorly controlled asthma. Reference: Simpson JL, et al . Inflammatory subtypes in asthma: assessment and identification using induced sputum. Respirology 2006;11(1):54–61.